Effect of Market Orientation and Innovation Toward Competitive Advantage In Business Street Food at Jl. Pahlawan Kusuma Bangsa Kediri City - Afif Nur Rahmadi; B. Dewandaru (Jurnal Bisnis dan Keuangan, 2021)
This study aims to determine the effect of market orientation and innovation on competitive advantage partially and simultaneously. The population in this study are MSME entrepreneurs who sell food on Pahlawan Kusuma Bangsa Street, Kediri, with a sample size of about 100 respondents. Based on the results of data analysis and discussion conclusions can be drawnthat partially market orientation and innovation posited with the highest or dominant value is market orientation. While simultaneously market orientation and innovation together affect competitive advantage. This is very good, by increasing market orientation and innovation, the company's competitive advantage will also increase. Therefore, market orientation and innovation variables are always improved so that food entrepreneurs who are on the way of the Heroes of Kusuma Bangsa can survive and increase competitive advantage.